Kebijakan Hukum Pendirian Yayasan Oleh Warga Negara Asing Di Indonesia - Muhammad Rizqullah Dany Putranto; Nabila Aulia Rizki; Naufandiary Bachtiar Ramzy (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The dynamic recognition of foundation legal entities in Indonesia has provided significant legal certainty, in accordance with Law Number 16 Year 2001 on Foundations which was amended through Law Number 28 Year 2004. However, it should be noted that this development reaches aspects of the establishment and management of foundations that relate to the participation of foreign nationals in establishing foundations in Indonesia. This research is a legal doctrinal research that adopts a statutory and conceptual approach. The findings of this research imply that Foreign Nationals who intend to establish a foundation in Indonesia can do so by complying with the provisions set forth in the prevailing laws and regulations. In addition, they can also assume a role in the foundation by fulfilling the conditions that have been set, with serious consequences to be faced if the conditions are not complied with. A possible consequence is the deportation of Foreign Nationals back to their country of origin.